Sistem Tilang Otomatis Jembatan Timbang Menggunakan Node MCU ESP8266 - Muhammad Ahsan Fauzi; Nasrulloh Nasrulloh; Edmud Ucok Armin (Journal of Electronic and Electrical Power Applications, 2021)
Weigh bridges currently have not played an optimal role. This is because there are still many truck transportation service users who fill vehicles that exceed the allowable limit (overload) and often encounter cases of illegal levies made by unscrupulous policy makers and business actors in order to pass vehicles that do not comply with the rules. The purpose of this research is to design and build a weighbridge system prototype for IoT-based truck load logistics vehicles and to create an automatic proof of violation system for truck drivers or other logistics vehicles with excess loads. The research method used is the Research and Development method. The results of this study are to produce a tool in the form of a weighbridge automatic ticket system prototype using the internet of things that can be integrated with the system owned by policy makers from the central to the regions, and also the system can issue proof of violation notifications to drivers directly without any illegal fees. Based on the results of tests carried out on the prototype using the JBI 35gram assumption, if the measured truck load exceeds 35 grams, it will send a proof of violation notification on the telegram and if appropriate, JBI will send a notification to continue the trip to the driver.